The performances of M4 generation of Mentik Susu rice mutants irradiated with gamma-ray - Wafa’ Nur Hanifah; Parjanto PARJANTO; Sri Hartati; ahmad yunus (Society for Indonesian Biodiversity, 2020)
Abstract. Hanifah WN, Parjanto, Hartati S, Yunus A. 2020. The performances of m4 generation of Mentik Susu rice mutants irradiated with gamma-ray. Biodiversitas 21: 4041-4046. Mentik Susu is local rice from Magelang, Central Java, Indonesia. It has superiority, in terms of soft texture and white color, but on the other hand, this local rice has the disadvantage of having relatively high stems, low yield, and long life. One way to overcome the weakness of Mentik Susu rice is by mutating plants using gamma-rays. The purpose of this research was to study M4 mutants from Mentik Susu rice irradiated with gamma-ray and to select mutans that have short stem and high productivity. The study was conducted using a simple random design experiment by planting various strains of M4 generation of Mentik Susu rice irradiated with 100 Gy and 200 Gy gamma-rays. T-test was employed to test the difference between strains treated with gamma-ray irradiation and control samples (without gamma-ray irradiation). The results showed that the M4 Mentik Susu rice irradiated with 100 Gy and 200 Gy gamma-rays in overall had lower stems, shorter flowering and harvesting ages, and higher productivity than non-irradiated Mentik Susu rice (control). The strains with the shortest stem and with highest yield productivity was resulted from 200 Gy gamma-ray irradiation with code of M-MS200-G15T3-2. This study also selected 30 individual mutant plants that had short stems and high productivity, suggesting that these plants can be passed to M5 generation.